2009
DOI: 10.1177/000348940911801109
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Trachea with Fibroblasts in a Rabbit Model

Abstract: This study indicated that fibroblasts had a stimulatory effect that hastened regeneration of the epithelium in large tracheal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Okano et al reported that measurement of the average thickness of the regenerated epithelium showed that the tracheal fibroblasts accelerated regeneration of the tracheal epithelium [7]. In the present study, the difference in the thickness of the epithelial layer was observed at 7, 14, and 28 days post-implantation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Okano et al reported that measurement of the average thickness of the regenerated epithelium showed that the tracheal fibroblasts accelerated regeneration of the tracheal epithelium [7]. In the present study, the difference in the thickness of the epithelial layer was observed at 7, 14, and 28 days post-implantation.…”
Section: Discussionsupporting
confidence: 55%
“…In response to this problem for regenerative medicine of the trachea, our group developed a collagen sponge scaffold with cultured fibroblasts, adipose tissue-derived stem cells, and induced pluripotent stem cells into rat or rabbit tracheal defects and reported the effective epithelial regeneration [6][7][8][9][10][11]. To promote regeneration of the tracheal epithelium without a cell source, we developed a collagen vitrigel scaffold possessing a smooth surface to facilitate epithelial cell migration after implantation [12].…”
Section: Introductionmentioning
confidence: 99%
“…7 To promote regeneration of the tracheal epithelium, our group has studied the effects of fibroblasts, adipose-derived stem cells, and basic-fibroblast growth factor in artificial grafts and shown that they shorten the time for epithelialization and cilia formation. [8][9][10][11][12][13][14] Collagen scaffolds are widely used in regenerative medicine because of their high biocompatibility, but no studies have examined the most suitable structure of collagen scaffold for tracheal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…63 Differentiated targets for reepithelialization have reported success with tracheal epithelial cells, tracheal fibroblasts, gingival fibroblasts, buccal mucosa, and skin. 3,8,26,28,29,49,64,65 …”
Section: Discussionmentioning
confidence: 99%
“…However, complete epithelialization has been observed in constructs using bone marrow–derived mesenchymal stem cells (BM-MSC), autologous epithelial cells, buccal mucosal graft, or tracheal fibroblasts. 6,8,29,49 It is unclear if respiratory epithelialization represents survival of donor epithelium or regeneration by the recipient modulated by a paracrine effect from seeded cells. However, epithelial migration from the anastomotic sites has been demonstrated in some studies, suggesting recipient derived neotissue.…”
Section: Discussionmentioning
confidence: 99%